Climate change impact and adaptation for wheat protein - Asseng, Senthold; Martre, Pierre; Maiorano, Andrea; Rötter, Reimund P.; O’Leary, Garry J.; Fitzgerald, Glenn J; Girousse, Christine; Motzo, Rosella; Giunta, Francesco; Babar, Muhammad Ali; Reynolds, Matthew P.; Kheir, Ahmed; et al. (Wiley, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO2. Introducing genotypes adapted to warmer temperatures (and also considering changes in CO2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.